دور الفايسبوك في نشر الوعي الديني لدى الأفراد: دراسة على بعض الصفحات الفايسبوكية المتخصصة. - رفاس, الوليد (جامعة الوادي - University of Eloued, 2022)
تحاول هذه الدراسة التعرف على طبيعة الدور الذي يقوم به موقع الفايسبوك في نشر الوعي الديني لدى مختلف أفراد المجتمعات العربية والإسلامية، وذلك من خلال تسليط الضوء على بعض الصفحات الفايسبوكية المتخصصة في نشر مضامين الدين الإسلامي، والتي تسعى إلى مواجهة العديد من الصفحات الفايسبوكية المجهولة المصدر والتي تنشر كل أشكال الإلحاد والكفر والخرافات والبدع والانحلال الخلقي، وكل ما يُهدد ويشوه ديانة الشعوب العربية والإسلامية. ومن أجل الوصول إلى نتائج ميدانية متعلقة بموضوع الدراسة، تم أخذ عينة من الصفحات الفايسبوكية الدينية التي تشهد متابعات واسعة من قبل مستخدميها، بلغ عددها ثمانية (08) صفحات، حيث تمت معاينتها وتحليلها، للخروج بنتائج تشرح طبيعة الدور الذي يقوم به الفايسبوك في نشر الوعي الديني لدى الأفراد المستخدمين له. This study attempts to identify the nature of the role that Facebook plays in spreading religious awareness among the various members of Arab and Islamic societies, by shedding light on some Facebook pages specialized in disseminating the contents of the Islamic religion, which seek to confront many anonymous Facebook pages that It spreads all forms of atheism, infidelity, superstitions, heresies and moral decay, and everything that threatens and distorts the religion of the Arab and Islamic peoples. In order to reach field results related to the topic of the study, a sample of the religious Facebook pages that witness extensive follow-ups by their users, amounted to eight (08) pages, where they were previewed and analyzed, to come up with results explaining the nature of the role that Facebook plays in spreading awareness religion of the individuals who use it.
The role of Facebook in spreading religious awareness among individuals: Study on some specialized Facebook pages.
مقال
Keywords: الدور ، الفايسبوك ، نشر ، الوعي الديني; role , Facebook, dissemination , religious awareness